Digital Solutions For Migration Management: Mobility And Integration - Sargsyan, Anush (ՀՀ ԳԱԱ ՏԻ)
Nowadays, human migration, driven by the pursuit of better opportunities, is a complex global phenomenon increasingly shaped by technology. This article examines the impact of digital platforms and artificial intelligence (AI) tools on the migration process, particularly their role in facilitating access to essential services such as healthcare and education and supporting migrants' integration into new communities. The study shows the role of digital platforms in managing and facilitating migration flows and compares globally used technologies with those available in Armenia, identifying areas for improvement. By analyzing how digital solutions streamline migration processes and enhance management, this article provides valuable insights for policymakers and organizations aiming to support migrants more effectively. Արդի պայմաններում մարդկային միգրացիան համաշխարհային բարդ երևույթ է, որն ավելի ու ավելի մեծ ազդեցության է ենթարկվում տեխնոլոգիաների կողմից։ Այս հոդվածում ուսումնասիրվում է թվային հարթակների և արհեստական բանականության (ԱԲ) գործիքների ազդեցությունը միգրացիոն գործընթացների վրա, մասնավորապես դրանց դերը առողջապահության և կրթության հիմնական ծառայությունների մատչելիության ապահովման, ինչպես նաև նոր համայնքներում միգրանտների ինտեգրման հարցում։ Ներկայացվում է թվային հարթակների դերը միգրացիոն հոսքերի կառավարման և հեշտացման գործում, ինչպես նաև համեմատվում են համաշխարհային մասշտաբով կիրառվող տեխնոլոգիաները Հայաստանում հասանելի գործիքների հետ՝ բացահայտելու բարելավման հնարավոր ոլորտները։ В настоящее время человеческая миграция, вызванная стремлением к лучшим возможностям, представляет собой сложное глобальное явление, которое все больше формируется технологией. Эта статья исследует влияние цифровых платформ и инструментов искусственного интеллекта (ИИ) на миграционный процесс, в частности их роль в упрощении доступа к основным услугам, таким как здравоохранение и образование, а также в поддержке интеграции мигрантов в новые сообщества.
Keywords: Migration